2011
DOI: 10.1007/bf03404876
|View full text |Cite
|
Sign up to set email alerts
|

Mumps Virus Detection During an Outbreak in a Highly Unvaccinated Population in British Columbia

Abstract: Mumps is an acute viral illness characterized by fever and parotitis that typically affects young children. 1 Clinical manifestations start with a non-specific prodrome, which can include malaise and headache, and are followed by painful swelling of the parotid glands. Less common presentations include epididymo-orchitis, oophoritis, pancreatitis and meningoencephalitis. Approximately half of those infected develop classical disease, the remainder having non-specific or respiratory symptoms and 15-20% being as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
7
3
0
Order By: Relevance
“…Our study also confirmed that rRT-PCR sensitivity varied with specimen type and was higher for buccal than oropharyngeal swabs or urine. This is consistent with previous studies showing that saliva swabs performed better than pharyngeal swabs, whereas test sensitivity was lowest for urine [ 4 , 23 , 37 ]. Similarly, Hindiyeh et al showed that RT-PCR sensitivity was higher with pharyngeal or parotid fluid than urine [ 38 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study also confirmed that rRT-PCR sensitivity varied with specimen type and was higher for buccal than oropharyngeal swabs or urine. This is consistent with previous studies showing that saliva swabs performed better than pharyngeal swabs, whereas test sensitivity was lowest for urine [ 4 , 23 , 37 ]. Similarly, Hindiyeh et al showed that RT-PCR sensitivity was higher with pharyngeal or parotid fluid than urine [ 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, IgM serology was significantly less sensitive than both rRT-PCR and viral culture. Our observed order of assay sensitivity is consistent with large studies with > 80 laboratory confirmed cases [ 3 , 5 , 23 , 24 ]. In addition, a number of studies have shown a better sensitivity of rRT-PCR compared to IgM serology [ 4 , 25 – 32 ] and, to a lesser extent, culture [ 12 , 25 , 26 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previously in BC, three outbreaks of mumps occurred in 1997, 2008, and 2011, largely affecting two populations: unimmunized faith-based communities and young adults in a susceptible cohort that received only one dose of mumps-containing vaccine as part of routine childhood immunization (11,12). Based on small hydrophobic (SH) gene sequencing, the 2008 and 2011 outbreaks were found to be caused by a genotype G strain; this is the most commonly circulating genotype identified in Europe and North America (13).…”
mentioning
confidence: 99%
“…In Canada, including BC, it is recommended that specimens be collected within 5 days of symptom onset when the viral load is highest (5,12). However, mumps virus RNA can be detected in buccal swabs up to 9 days after symptom onset (11), although oral virus shedding may be limited to the first 2 to 3 days in vaccinated individuals (20)(21)(22). Simultaneous collection of a urine sample can improve the detection yield when the patient presents more than 5 days after symptom onset since mumps RNA is shed in urine longer (11).…”
mentioning
confidence: 99%